Circ_0008035 Promotes Gastric Cancer Development via the miR-429/SMAD2 Cascade - Chen, Yan; Bian, Weigang; Chen, Surong (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The vital roles of circular RNAs (circRNAs) in human tumorigenesis have attracted more attention. Circ_0008035 is one of the most up-regulated circRNAs in gastric cancer (GC). Herein, we explored the associated mechanism of circ_0008035 in GC. Materials and Methods: EdU incorporation experiments were performed to monitor cell proliferation ability. Cell cycle progression, apoptosis, angiogenesis, migration, and invasion were analyzed using flow cytometry, Tube formation, and Transwell assays respectively. Protein expression was detected by Western blot. Dual-luciferase reporter experiments were applied to demonstrate the relationship between circ_0008035 or SMAD family member 2 (SMAD2) and microRNA-429 (miR-429). Mouse xenograft assays were conducted for evaluation of the role of circ_0008035 in vivo. Results: Circ_0008035 content was elevated in GC tissues (P < .0001) and cell lines (P < .001), and its deficiency hindered GC cell proliferation (P < .01), HUVEC angiogenesis (P < .05), and GC cell metastasis (P < .01) and triggered apoptosis (P < .01). Circ_0008035 could sponge miR-429 to up-regulate SMAD2 expression (P < .0001). Circ_0008035 absence restrained tumor growth in vivo (P < .01). MiR429 was a mediator of circ_0008035 function, and miR-429 hindered GC cell malignant phenotypes by SMAD2. Conclusion: Circ_0008035 aggravates GC cell malignant progression partially by targeting the miR-429/SMAD2 axis. Considering the inhibitory effect of circ_0008035 deficiency on GC progression, targeting circ_0008035 may be a potential approach to prevent or treat GC. Cite this article as: Chen Y, Bian W, Chen S. Circ_0008035 promotes gastric cancer development via the miR-429/SMAD2 cascade. Turk J Gastroenterol. 2024;35(10):795-804.